Pengaruh Pembelajaran Organisasional, Orientasi Pasar dan Inovasi Organisasi terhadap Keunggulan Bersaing (Studi pada PT Bank Rakyat Indonesia (Persero) Tbk. Cabang Malang Raya - Hapsari, Gusti Ruzayda Eka; Hadiwidjojo, Djumilah; Thoyib, Armanu (Universitas Brawijaya, Indonesia, 2014)
The purpose of this study to analyze the influence of organizational learning, market orientation and organizational innovation to competitive advantage. Population of this research is the head unit PT Bank Rakyat Indonesia (Persero) Tbk Branch Malang with a sample of 64 respondents. Analysis of the data in this study using multiple regression. The results show that organizational learning, organizational, innovation and market orientation significantly influence competitive advantage. In order to gain a competitive advantage, then the leader must be able to increase the capacity of learning, by providing the opportunity to enhance their knowledge about ways to work better through education and training, in addition to develop themselves in the field of science and technology. As well as cultivate discussions in groups. in solving problems at work, leadership always pay attention to the orientation of the market by focusing on the quality of services provided by competing banks. This is done as an evaluation for improvement, do develop or innovation related to banking information system, in addition to redevelop products/ services that already exist on an ongoing basis, such as Core Banking System (CBS), Electronic Banking, Enterprise Data Model, Business Continuity Plan and Disaster Recovery Plan, and communicates availability Network Security System.